Directing Group Assisted Unsymmetrical Multiple Functionalization of Arene C−H Bonds. Issue 9 (11th August 2020) - Ghosh, Koushik; Rit, Raja K.; Shankar, Majji; Mukherjee, Kallol; Sahoo, Akhila K.
Abstract: Multiple C−H bond functionalizations promptly install diverse groups on the molecular framework and consequently fabricate complex molecular entities. This review briefly surveys the conceptual development of directing group assisted unsymmetrical multiple functionalization of arene C(sp 2 )−H bonds, which is exceedingly appealing and highly important. Abstract : This review briefly summarizes a systematic development of directing group assisted unsymmetrical multiple functionalization of arene C(sp 2 )−H bonds. The domino multiple C−H functionalization gives a straightforward access to complex molecular architecture.